Employability Skills Requirements in the Professional Services Sector: An In-depth Analysis of Graduates - Aguenza, Benjamin B.; Ingles, Cathlene D. (International Journal of Entrepreneurship and Sustainability Studies, 2024)
In today’s competitive job market, the gap between academic preparation and industry expectations has become increasingly evident, highlighting the urgency of identifying the key employability skills required by graduates.  This study evaluates the essential employability skills of graduates in the professional services sector. Using a descriptive research design, a questionnaire was administered to 282 respondents in the Philippines.  The sample size was determined using Slovin's formula and a stratified random sampling technique. Data analysis involved frequency percentage distribution, weighted mean, and analysis of variance (ANOVA).  Findings reveal a significant proportion of respondents as team leaders, holding bachelor’s degrees, and working in professional services firms with more than 151 employees. Effective communication skills emerged as the foremost requirement, complemented by leadership skills that foster enthusiasm and commitment within organizations.  Notably, disparities in employability skills were found when respondents were categorized based on organizations’ sizes. Concurrently, respondents reported challenges in articulating well-defined career objectives and demonstrating adaptability.  These findings underscore the imperative for higher institutions to emphasize curricula that enhance graduates’ employability skills, particularly in communication, leadership, critical thinking, and problem-solving. Universities should tailor their academic programs to strengthen these crucial skills, benefiting both graduates and the professional services industry.  Furthermore, continuous professional development and industry-academic partnerships are recommended to keep curricula aligned with evolving industry needs, ensuring that graduates are well-equipped for the dynamic job market.